Pelatihan membuat media pembelajaran bagi Guru TK di Kabupaten Gowa - Syafiuddin Parenrengi (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The problem faced by kindergarten/early childhoodteachers is that the teachers cannot make computer-assistedlearning media. The learning media used are still drawn by theteacher themselves which does not interest students as not allteachers are able to draw well. The computer-based learningmedia training for TK/PAUD teachers in Pattallassang GowaRegency. This conducted to make the teachers gain moreknowledge and skills on how to make or create learning mediathrough computer. In addition, they are also able to access theinternet via a computer. The target audience of this activitywere kindergarten/early childhood teachers who are membersof the IGTKI (Indonesian Kindergarten Teachers Association)Pattallassang District, Gowa Regency. The method used in thedelivery of material were lectures, discussions, question andanswer, demonstrations and simulations as well as direct workpractices. While the evaluation used was direct observation toparticipants when practicing making learning media andaccessing the internet. Based on observations, around 70%teachers could access the internet and make media properly.This activity could increase the knowledge and skills ofkindergarten teachers in accessing the internet and createlearning media with the benefits of computer applications.Furthermore, it is suggested to lecturers, especially those whoexpert in education, to provide counseling/training/mentoringprogram for teachers because the teachers still really need helpregarding improving their teaching performance.